The Effect of the Modified Eighth Section of Eight-Section Brocade on Osteoporosis in Postmenopausal Women: A Prospective Randomized Trial - Liu, Bao-Xin; Chen, Shu-Peng; Li, Yu-Dong; Wang, Ji; Zhang, Bin; Lin, Ying; Guan, Jun-Hui; Cai, Ying-Feng; Liang, Zhu; Zheng, Fang (Medicine (Baltimore), 2015)
Osteoporosis and related fragility fractures represent a serious and global public health problem. To evaluate whether the modified eighth section of Eight-section Brocade (MESE) exercise could improve the symptom and indexes associated with osteoporosis in postmenopausal women. Guangzhou and Liuzhou hospital of traditional Chinese medicine in China. Women (n = 198) aged 50 to 75 years were randomized into Control, Ca, MESE, and MESE + Ca. Subjects in Ca and MESE groups were separately asked to consume thrice daily Calcium Carbonate Chewable D3 tablet and to perform thrice daily MESE exercise by 7 repetitions per time for 12 months. Subjects in MESE + Ca group performed such the combined treatment project for 12 months. Body height and Hospital for Special Surgery (HSS) scores of both knees, chronic back pain visual analogue scale scores (VAS), bone mineral density (BMD) at L2 to L4 and the left femoral neck, 3-feet Up and Go Test (3') and one-leg Stance (OLS). In our study, the improvement in chronic back pain of the patients in Ca, MESE, and MESE + Ca group was better than that in control group. There was 1.9% and 1.7%, 2.3%, and 2.1% net profit in left femoral neck and lumbar BMD after the treatment for 12 months in MESE and MESE + Ca groups. For the balance capacity, the subjects in MESE and MESE + Ca groups secured much better performance than those in Ca and control group after the treatment for 12 months (P < 0.001, P < 0.001). The treatment of MESE exercise is the most effective for the improvement of the symptom and indexes in postmenopausal women. Importantly, the low attrition and the high exercise compliance indicate that MESE exercise is safe, feasible, and well tolerated by postmenopausal women.